DELINEATION OF WOMEN IDENTITY IN THE DISNEY ANIMATED FILM ECANTO (2019) - Agustin Diana Wardaniningsih; E. Ngestirosa Endang Woro Kasih (Lire Journal (Journal of Linguistics and Literature), 2022)
Disney's animated films is produced not only to provide entertainment but also to deliver messages in it. Most Disney animated films have a target audience of children. The element of persuasion that includes every message will be one of children's character-building in real life, including how the film constitutes gender identity in children, which will affect the development of their lives. One of Disney's animated films is Encanto film which was released in 2021. The purpose of this research is to describe the moral values of the characters in Encanto film, especially observing the identity of the women depicted in this film. The research method uses a qualitative narrative approach to analyze Encanto film. This study uses Stuart Hall's representation theory and Christian Metz's Semiotic Analysis Method (MAS), or cinematographic semiotics. By the critical paradigm, this MAS is qualitatively interpretive. A method that focuses on signs and texts as objects of study and how researchers interpret and understand the code (decoding) behind the signs and texts. The study revealed the women's identity on the main character, Mirabel in the film Encanto. This identity is mainly found from the stereotypical Mirabel identity as a woman. The other marginalization, subordination, power, and workload differentiate Mirabel’s identity as a woman from men in Encanto film